Membangun Pendidikan Berkualitas Melalui Kepemimpinan Kepala Sekolah dan Penerapan Kurikulum Merdeka - Putri Yulianti Rahmalinda; Nadhira Azzahra; Yessi Rifmasari (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This research aims to study the role and position of the principal as a leader in implementing the Independent Learning program in elementary schools and the influence of this leadership on the success of achieving educational goals. Apart from that, this also shows that the principal's leadership plays a strategic role in determining the success of educational goals. This research uses literature research methods and data is obtained by analyzing various sources such as books, scientific journals, articles and other documents related to the research subject. The study shows that the leadership of the school principal is very important to support the implementation of Merdeka Belajar. As leaders, they are responsible for setting policies, creating an educational vision that is aligned with national goals, and optimizing existing resources to create a good learning environment. The Independent Learning Program, which was founded by the Minister of Education, Culture, Research and Technology Nadiem Makarim, aims to realize the Pancasila Student Profile by producing students with superior character. Religious values, global diversity, independence, creativity and critical thinking are part of this profile. The success of the Merdeka Belajar program really depends on school principals who are good at managing education policies at the school level. With good leadership, school principals can incorporate the principles of Independent Learning into the elementary school curriculum and make a real contribution to achieving educational goals.